Analysis Of Dryer Control System For Non-Conformity Of The Crumb Rubber Products In PT. Bukit Angkasa Makmur Bengkulu - Prastia, Budi; Bursamin, B; Fernandes, Regi; Hidayad, Syamsir (Universitas Muara Bungo, 2025)
Objective: This study aims to determine the rubber latex processing system into SIR 20 (Standard Indonesian Rubber) type products that involve several main stages, including initial processing, drying, and quality control. The dryer machine plays an important role in the drying process to achieve the desired quality standards, especially the dry factor to produce products that meet the technical standards of rubber specifications. Research Method: This study uses data collection techniques in the drying process. Data is taken periodically during the drying process in the form of temperature data, water content, dryer oven including primary and secondary data. Results: The results of the study indicate an impact on the quality of SIR products in the dryer process that affects product quality such as low water content, uniform particle size so that the drying process is more effective, reduces operational costs, and produces high-quality final products. While the quality of products with poor quality such as high water content, non-uniform particle size, many impurities will reduce the productivity of the drying process, increase operational costs, and produce lower-quality final products. Conclusion: There are several factors that affect the quality of SIR 20 (Standard Indonesian Rubber 20) rubber products on the performance of the dryer machine is closely related to drying efficiency and the final quality of the product. SIR 20, as crumb rubber, has several characteristics that influence the drying process, such as initial moisture content, particle size, and type of impurities. Good dryer performance will produce SIR 20 with a moisture content that meets standards, reduce the risk of damage during storage and transportation, and maintain its physical and chemical quality. To prevent product deviations, monitoring the drying time and energy supply is necessary to achieve the desired dryness through proper coagulation and processing. Consideration of crumb rubber particle size is essential for effective drying and to prevent clumping and difficulties in hot air distribution. Article Type: Empirical Research Article